Gait Feature Based on Human Identification & Classification by Using Artificial Neural Network and Project Management Approaches for Its Implementation - Tariq, Waqar; Lutfi Othman, Muhammad; Akhtar, Shameem; Tariq, Fareeha (International Journal of Engineering and Technology, 2019)
With the increased threat of terrorism and identity theft, human recognition is one of the basic elements of present eraâ€™s security applications installed in commercial malls, banks, hospitals, military installations, airports, religious places etc. The basic aim of this research study is to design and implement an ANN based human recognition and monitoring system.Â This system uses Gait property of people to classify them through their age, gender, and group. Furthermore, the implementation and testing phase is conducted according to the principle and approaches of Project Management in order to tackle the constraint of both time and cost, also to make it a well implemented ICT project which can also follow the same approach as used commercially .Taking a tracking approach of the cost, time and quality made it easy to judge that this project is commercially viable.Â Â